VALUE-BASED MANAGEMENT AND CORPORATE GOVERNANCE: A STUDY OF SERBIAN CORPORATIONS - Stančić, Predrag; Todorović, Miroslav; Čupić, Milan (Economic Annals, 2012)
The aim of this paper is to determine the place and role of corporate governance and performance measures in the efforts of managers to maximize shareholder value, and the attitude of Serbian corporations toward these issues. The paper first analyses the importance of corporate governance and performance measures in the context of value-based management. Then, through the multiple case study, we investigate the attitude of seven Serbian corporations toward defining the general corporate objective, corporate governance, and performance measurement. Finally, we point out the factors and preconditions that determine corporate culture, objective definition, and performance measures used by Serbian corporations.